Oxymatrine inhibits non–small cell lung cancer via suppression of EGFR signaling pathway. (13th December 2017) - Li, Wei; Yu, Xinfang; Tan, Shiming; Liu, Wenbin; Zhou, Li; Liu, Haidan
Abstract: Epidermal growth factor receptor (EGFR) plays a crucial role in human non–small cell lung cancer (NSCLC) tumorigenesis. In this study, oxymatrine was identified as an EGFR signaling pathway inhibitor in NSCLC. Oxymatrine inhibited anchorage‐dependent and independent growth of NSCLC cell lines but had no cytotoxicity in normal lung cells. We found that exposure to oxymatrine not only suppressed the activity of wild‐type EGFR but also inhibited the activation of exon 19 deletion and L858R/T790M mutated EGFR. Flow cytometry analysis suggested that oxymatrine‐induced cell cycle G0/G1 arrest was dependent on EGFR‐Akt signaling. Exogenous overexpression of Myr‐Akt rescued cyclin D1 expression in HCC827 cells. Moreover, oxymatrine prominently suppressed tumor growth in a xenograft mouse model. Thus, oxymatrine appears to be a novel therapeutic agent for NSCLC treatment. Abstract : For the first time we discovered that oxymatrine inhibited the activation of both wild‐type and mutant epidermal growth factor receptor (EGFR). Mechanism studies demonstrated that the inhibition of cell proliferation by oxymatrine was mainly attributed to its effect on EGFR‐Akt‐cyclin D1 signaling pathway.